Extraction and Analysis of Plant Active Ingredients - Reverchon, Ernesto (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The extraction of active ingredients from vegetable matter is one of the most attractive research fields in the literature. A perspective that promotes this large interest is the possibility of identifying eco-friendly and innovative processes, active products, and materials. However, care must be taken in selecting process arrangements and extraction conditions to minimize the co-extraction of undesired compounds. The analysis of the composition of the extracted compounds by chromatography, mass spectrometry and related techniques, is a relevant step in determining the performance of the extraction process and the purity of the extracted compounds to be used for pharmaceutical applications.This reprint includes 10 Research papers, 1 Communication, and 1 Review, and reports innovative extraction techniques and advanced analytical methods used for the recovery and the identification of high-added value compounds from vegetable matter.